Study of synthetic jets in boundary layers - Wen, Xin (2015)
As a zero-net-mass-flux actuator, a synthetic jet (SJ) actuator is a promising active flow separation control device. In order to make this technology more feasible in real-world applications, this research aims to uncover more underlying physics associated with SJ-based flow separation control. Both a CFD framework and a water-tunnel platform are developed, and decomposition methods are applied to extract coherent flow structures. It is found that the single-SJ-induced hairpin vortex in the turbulent boundary layer (TBL) is asymmetric, oscillates laterally, and dissipates fast, whereas it is symmetric and persistent in the laminar boundary layer (LBL). Using in line twin SJs in attached LBLs, three types of vortex structures are identified at various operational phase differences: one combined vortex at 90 degree, two completely separated vortices at 270 degree, and partially interacting vortex structures at 0 and 180 degree. Distinct flow control effect is found by applying these vortex structures on a separated LBL.